Perancangan Materi Promosi Event Ramadhan Jazz Festival 2018 - Dianti Puspita Nurshadrina (Fakultas Ilmu Komputer Universitas Nahdlatul Ulama Sidoarjo, 2018)
Each year, the number of music festivals held in Jakarta area increases. One of them is Ramadan Jazz Festival, held by RICMA and Warta Jazz. This music festival attracts millennial people to come to the mosque in a different way, by joining a jazz festival in Jakarta that can be attended by Muslims or non-Muslims. Music festivals can be well organized if they have appropriate promotional materials. The promotional materials used must have an appropriate design, as well as the right elements for the message delivered by the organizers being delivered properly, so that the interest of the audience also increases. Keywords: Promotional materials, music festivals, visual communication design, layout, typography